Acquisition of Morphological Rules for Plural Allomorphs in Kannada -A Pilot Study - Subrahmanyaiah MG (Journal of All India Institute of Speech and Hearing, 1970)
This study was conducted to evaluate  the  acquisition of morphological rules in children using a test developed in Kannada. This test is based on the"Wug Test " developed by Jean Berko in English. Fourteen children (seven boys and seven girls) were used as subjects. The age range of these children was 9-10 years. Three kinds of plural allomorphs which are used by both adults and children to indicate plural forms were studied. 'Cloze' technique was used  to assess knowledge of morphological rules. The results have been analysed and discussed.